Remaking a European, Post-catastrophic Atmosphere in 2000s China: Jia Zhangke’s Still Life, Iconology and Ruins - Ramos Monteiro, Lúcia (Cinémas, 2015)
Jia Zhangke’s Still Life (Sānxiá hǎorén, 2006) was shot in Fengjie, shortly before its flooding brought about by the construction of the Three Gorges Dam, the world’s largest hydropower station in terms of capacity. The film remakes the post-apocalyptic atmosphere found in European films made after the Second World War. From a web of cinephilic, intermedial and intertextual references, which inscribes Still Life in a local and global history of art and of film, this text compares the way Jia films his characters in a disappearing Fengjie with sequences from Roberto Rossellini’s Germany Year Zero (Germania anno zero, 1948) and Michelangelo Antonioni’s Red Desert (Il deserto rosso, 1964). While remaking the composition of ruins framing Edmund, in the first case, and in the second, a complex relation between background and figure in a deserted industrial landscape, Still Life creates a strange temporality, combining the imminence of a future catastrophe with the memory of past ones.